Global disease burden due to antibiotic resistance - state of the evidence - Mark Woolhouse; Catriona Waugh; Meghan Rose Perry; Harish Nair (Edinburgh University Global Health Society, 2016)
The absence of comprehensive and reliable estimates of the global health burden due to antibiotic resistance makes it difficult to assess trends and harder to justify the allocation of adequate resources to deal with the problem.